LEGAL PROTECTION FOR CUSTOMARY COMMUNITIES IN THE SETTLEMENT OF DISPUTES OVER LAND TENURE AND UTILIZATION WITH OIL PALM PLANTATION ENTREPRENEURS - Samsul Bahri; Dina Paramitha Hefni Putri; Heribertus Richard; Isnawati (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study analyzes legal protection for indigenous peoples in disputes over land ownership and utilization with oil palm plantation entrepreneurs through a normative study of customary rights, the principle of legal certainty, and dispute resolution mechanisms based on Indonesian agrarian law. Constitutionally, Article 18B paragraph (2) and Article 33 paragraph (3) of the 1945 Constitution recognize the rights of indigenous peoples and emphasize that control of natural resources by the state must be directed to the greatest possible prosperity of the people. However, in practice, the granting of Cultivation Rights (HGU) and plantation business permits often gives rise to structural conflicts due to weak administrative recognition of customary areas and unequal bargaining positions. This study uses normative legal methods with a statutory, conceptual, and case approach, including analysis of Constitutional Court decisions and PTUN jurisprudence. The results of the study indicate that legal protection for customary rights is still declarative and does not provide substantive legal certainty. Strengthening legal protection requires regulatory harmonization, formal recognition of customary areas, and reform of dispute resolution mechanisms based on agrarian justice and the principle of the public trust doctrine.